Complementary Therapy to The Mental Health of Postpartum Mothers - Noviyati Rahardjo Putri (Prodi DIII Kebidanan Blora Poltekkes Kemenkes Semarang, 2023)
Postpartum mothers can experience positive and negative emotional changes. Mother's positive emotions include joy, happiness, satisfaction while negative emotions include anxiety, frustration, confusion, sadness and guilt in undergoing role changes. Therapy is needed to shape the mother's coping skills in dealing with emotional changes during the puerperium, one of which is complementary therapy. The aim of the study was to analyze various scientific literacy related to complementary therapies given with the aim of maintaining the health of postpartum mothers. This research method is a literature review. Data is accessed from various database sources; Google Scholar, PubMed, Science Direct, Sage Pud, ProQuest in the period 2013 to 2023. The main topic search keywords are; complementary therapy, mental health and postpartum period. The results of this study concluded that complementary therapies in the form of intervention music, laughter therapy, yoga, therapeutic touch, acupressure, reflexology, massage, aromatherapy and herbal therapy statistically can improve women's mental health in the postpartum period. In the future, interventions with complementary therapies can be used on a larger research sample scale.